Hak Pasien Untuk Didampingi Keluarga Dalam Pelayanan Kesehatan (Kajian Yuridis Undang-Undang Nomor 44 Tahun 2009 Tentang Rumah Sakit) - Supeno Supeno; Warfian Saputra (Universitas Batanghari Jambi, 2018)
Increasing public awareness of the importance of health then protection against patients in Hospitals is a very important issue for review because it has been going on a wide variety of acts committed by the parties of certain detriment of patients such as the occurrence of sexual harassment in the service of health, this happens because the patient did not receive the full accompaniment of families in Ministry of health, legally this right is not set explicitly in the Act No. 44 of the year 2009 Of the hospital so that the patient's legally difficult to prove was the occurrence of sexual harassment against him, therefore this Act must give full rights to the patient for his family accompanied in each health service acquired in the hospital, a change in the law this is a thing that needs to be done immediately so that the patient gets legal protection so that similar cases could be minimised so that public confidence against the hospital will progressively increase.